Adoption of the AAOIFI International Code of Ethics for Indonesian Islamic Accountants - Haitam, R. Ibnu; Ardiansyah, Misnen; Salim, Mohammad (IKONOMIKA, 2021)
Accounting scandals against standards still occur in Indonesia. The Indonesian Islamic accounting code of ethics needs to be formulated in line with the development of Islamic accounting practices in Indonesia. The preparation of the Islamic accounting code of ethics needs to adopt the AAOIFI International Islamic accounting organization code of ethics. This study aims to describe the recommendations of scholars regarding the adoption of the AAOIFI code of ethics for Indonesian Islamic accountants. This research uses a qualitative type prioritizing interview techniques in collecting data. The study used the AAOIFI code of ethics through interviews with ulama (scholar) from the Indonesian Ulema Council (MUI). The results of this study are the adoption of the AAOIFI code of ethics provides guidelines for the preparation of a code of ethics for Indonesian Islamic accountants. The preparation of the code of ethics for Islamic accountants applies Islamic law in order to provide solutions to contemporary modern problems. The adoption of the AAOIFI International Code of Ethics takes into account the Indonesian urf am so that it is in accordance with existing financial accounting practices.